2020
DOI: 10.47210/bjohns.2020.v28i2.335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adenotonsillectomy on Weight Gain in Children

Abstract: Introduction ‘Failure to thrive’ is considered to be an indication for adenotonsillectomy in children. There is contrasting evidence regarding weight gain in children following adenotonsillectomy. The objective of this study is to evaluate weight change post adenotonsillectomy. Materials and Methods A prospective study conducted on 45 children of age between 5 to 15 years, who underwent adenotonsillectomy in our hospital. Weight is calculated at three different period i.e. preoperative, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The PRISMA flow diagram ( Figure 1 ) summarizes the study screening process. A summary of the studies included in this systematic review and the grading of evidence is reported in Table 1 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram ( Figure 1 ) summarizes the study screening process. A summary of the studies included in this systematic review and the grading of evidence is reported in Table 1 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%